2003
DOI: 10.4049/jimmunol.171.8.4011
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Regulation of Lymphocyte-Endothelial Interactions by Pregnancy-Associated Hormones

Abstract: Precursors of uterine NK cells home to the uterus during early pregnancy from multiple lymphohemopoietic sources. In mouse uterine tissue, pregnancy markedly up-regulates both L-selectin- and α4 integrin-dependent adhesion pathways for circulating human CD56bright cells, the phenotype of human uterine NK cells. Based on roles for these adhesion molecules in lymphocyte homing, we examined effects of pregnancy or the steroid hormones 17β-estradiol or progesterone on lymphocyte-endothelial interactions in seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 70 publications
2
53
0
1
Order By: Relevance
“…Although Peripheral CD16 ϩ NK cells also express CXCR4, as reported by Campbell et al (26), the intensity of CXCR4 on the peripheral CD16 ϩ and CD16 Ϫ NK cell surface, and the ability of these two NK cell subsets to migrate in response to CXCL12 are very likely different. More important, in humans circulating CD56 bright CD16 Ϫ NK cells express functionally active L-selectin at extremely high levels, compared with CD56 dim CD16 ϩ NK cells (33), and L-selectin is necessary in the adhesion of CD56 bright CD16 Ϫ NK cells to the decidualizing uterus (12,34 This report has demonstrated that trophoblast cells contribute to the recruitment of the decidual CD56 bright CD16 Ϫ NK cells. It should be noted that many adhesion molecules are expressed in uterine stroma and uterine stroma itself is capable of attracting circulating leukocytes, as distinct populations of immune cells migrate into the uterus during the course of the menstrual cycle (5,35).…”
Section: Discussionmentioning
confidence: 99%
“…Although Peripheral CD16 ϩ NK cells also express CXCR4, as reported by Campbell et al (26), the intensity of CXCR4 on the peripheral CD16 ϩ and CD16 Ϫ NK cell surface, and the ability of these two NK cell subsets to migrate in response to CXCL12 are very likely different. More important, in humans circulating CD56 bright CD16 Ϫ NK cells express functionally active L-selectin at extremely high levels, compared with CD56 dim CD16 ϩ NK cells (33), and L-selectin is necessary in the adhesion of CD56 bright CD16 Ϫ NK cells to the decidualizing uterus (12,34 This report has demonstrated that trophoblast cells contribute to the recruitment of the decidual CD56 bright CD16 Ϫ NK cells. It should be noted that many adhesion molecules are expressed in uterine stroma and uterine stroma itself is capable of attracting circulating leukocytes, as distinct populations of immune cells migrate into the uterus during the course of the menstrual cycle (5,35).…”
Section: Discussionmentioning
confidence: 99%
“…Both the fact that the T cell population from axillar nodes was not affected during DHEA-induced hyperandrogenization and that the T cell population from retroperitoneal lymph nodes was affected -and also the fact that hyperandrogenization induced a similar T cell population when samples from retroperitoneal lymph tissue were compared with those obtained from ovarian tissue -lead us to suggest that the local inflammatory status would be contributing to a selective differentiation of T cells. According to this hypothesis, lymph nodes and sex steroids are related to different systems, thus suggesting a coordinated organ-specific and steroid hormone relationship (Chantakru et al 2003). Moreover, the E receptor expressed by follicular dendritic cells in lymph nodes has recently been proposed as a novel pathological marker (Sapino et al 2003) and the deficiency of E caused by ovariectomy or menopause is involved in the T lymphocyte status (Safadi et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Further, NK cells from the same blood adhered to gd6-7 tissue as single cells but adhered in progressively larger clusters to sections from tissues of more advanced gestational ages [16]. These clusters did not adhere over the fetus or placenta but were found broadly across the decidua basalis, suggesting that a major functional change within the decidua basalis was being detected by the blood indicator lymphocytes.…”
Section: Introductionmentioning
confidence: 96%
“…Throughout our studies employing mouse decidua as an adhesion substrate, we noted that use of sections from more advanced pregnancies (gd 8-12) led to huge gains in numbers of adherent NK cells from a common blood sample, even when analysed on a single slide [16].…”
Section: Introductionmentioning
confidence: 99%